2012
DOI: 10.1007/s00167-012-2011-9
|View full text |Cite
|
Sign up to set email alerts
|

Changing sagittal plane body position during single-leg landings influences the risk of non-contact anterior cruciate ligament injury

Abstract: Leaning forward while landing appears to protect the ACL by increasing the shock absorption capacity and knee flexion angles and decreasing anterior shear force due to the knee joint compression force and quadriceps muscle activation. Conversely, landing upright appears to be ACL harmful by increasing the post-impact force of landing and quadriceps muscle activity while decreasing knee flexion angles, all of which lead to a greater tibial anterior shear force and ACL loading. ACL injury prevention programmes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
92
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 35 publications
(67 reference statements)
10
92
1
Order By: Relevance
“…16 We defined recreationally active as being involved in physical activities for at least 30 minutes per day, 3 times per week. All participants provided written informed consent, and the study was approved by the Institutional Review Board for the Protection of Human Participants at the University of North Carolina at Greensboro.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…16 We defined recreationally active as being involved in physical activities for at least 30 minutes per day, 3 times per week. All participants provided written informed consent, and the study was approved by the Institutional Review Board for the Protection of Human Participants at the University of North Carolina at Greensboro.…”
Section: Participantsmentioning
confidence: 99%
“…The men landed from a greater box height because their jump capacities are often greater than those of women [21][22][23][24] and because we confirmed that recreationally active men and women could successfully perform the 3 landing styles from these box heights. After digitization procedures were performed as described previously, 16 the participants were familiarized with single-legged drop landings until they were comfortable with all styles. Next, they performed 5 single-legged landing trials onto a force plate using each of the 3 different landing styles: selfselected (SSL), body leaning forward with a more plantarflexed position at foot contact (LFL), and body upright with a flat-footed position (URL).…”
Section: Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations